Sense of efficacy from student teaching to the induction year - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
This longitudinal study investigates the efficacy levels of Turkish prospective teachers of English from student teaching to induction year. Data from pre-service teachers enrolled at a state university in Istanbul revealed there was an increase in overall efficacy scores from before student teaching/BST phase to after student teaching/AST phase, which was followed with no significant change at the end of induction year. Changes in efficacy scores regarding student engagement, instructional strategies, and classroom management were also investigated during the same period and social persuasion, enactive mastery and vicarious experiences were found to contribute to teacher efficacy. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Pre-service teacher efficacy; novice teacher efficacy; student engagement; instructional strategies; classroom management; SELF-EFFICACY; BELIEFS